2009
DOI: 10.1089/jwh.2008.0966
|View full text |Cite
|
Sign up to set email alerts
|

Association between Provision of Initial Family Planning Services and Unintended Pregnancy among Women Attending an STD Clinic

Abstract: Certain baseline characteristics identified a subset of women seen in an STD clinic that were associated with future unintended pregnancy. Targeted interventions addressing these factors are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 8 publications
1
13
0
Order By: Relevance
“…9 Approximately 10%-20% of women attending STD clinics are pregnant. 11,12 The higher rates of alcohol use with pregnancy seen in STD clinics are not surprising. The highest levels of heavy alcohol use, and the highest incidences of Chlamydia trachomatis and Neisseria gonorrhoeae infections, have been found in 15-to 24-year-olds.…”
Section: Pcsi Principles and Std Clinicsmentioning
confidence: 99%
“…9 Approximately 10%-20% of women attending STD clinics are pregnant. 11,12 The higher rates of alcohol use with pregnancy seen in STD clinics are not surprising. The highest levels of heavy alcohol use, and the highest incidences of Chlamydia trachomatis and Neisseria gonorrhoeae infections, have been found in 15-to 24-year-olds.…”
Section: Pcsi Principles and Std Clinicsmentioning
confidence: 99%
“…Unintended pregnancies are similarly common in the general population [10][11][12][13]. The 2002 National Survey of Family Growth showed that 49% of pregnancies to women aged 18-44 years old in 2001 in the USA were unintended [10].…”
Section: Introductionmentioning
confidence: 99%
“…The U.S. Behavioral Risk Factor Surveillance System survey data showed that 29% of 18-to 44-year-old fertile women were at high risk for unintended pregnancy, based on the report of failure to use any form of contraception [11]. A 19% pregnancy rate was observed among a cohort of women seen in a sexually transmitted disease clinic in the USA, all of whom reported 'no intention of becoming pregnant' at their previous visit [12]. The 2008 Preconception Health Survey of 200 pregnant women and 151 women with a child under the age of 7 years living in Ontario, Canada, revealed that 30% of pregnancies were unplanned and 67% of women were happy with their last pregnancy [13].…”
Section: Introductionmentioning
confidence: 99%
“…Three of the studies were cross-sectional (Decker et al, 2012; Jones et al, 2006; Magnusson et al, 2011), two were prospective (Abrams, 1985; Upadhyay, Brown, Sokoloff, & Raine, 2012), one involved a retrospective chart review (Shlay, Zolot, Bell, Maravi, & Urbina, 2009), and one involved a pseudo cohort extracted from a randomized controlled trial by ignoring randomization (Cremer et al, 2011). …”
Section: Resultsmentioning
confidence: 99%
“…Two studies prospectively asked participants if they hoped to delay or avoid childbearing in the future (Cremer et al, 2011; Upadhyay et al, 2012). One study assumed that women desired to delay or avoid pregnancy based on request for contraception (Shlay et al, 2009). In these articles, the term “unplanned” was often used interchangeably with “unintended.” In a report by the National Center for Health Statistics, these terms were reported to frequently be used interchangeably in the literature (Mosher et al, 2012).…”
Section: Resultsmentioning
confidence: 99%